The performance management model of the integral teaching program (PEI) - training in context - Fodra, Sandra Maria; Nogueira, Maria Ephigênia Cáceres (Revista Hipótese, 2018)
The article presents the Performance Management Model of the Integral Education Program São Paulo State Departament of Education as a public educational policy that aims at the continuous formation in the context of the education professionals and its premise is the homology of development processes based on the ecological perspective of professional and organizational development of Bronfenbrenner. The education professionals (directors, coordinators and teachers) who enter the schools of this Program are appointed and do not hold bankrupt positions; They work on an exclusive dedication basis and receive a 75% salary bonus. Those interested are accredited on the website of the State Department of Education, undergo an initial interview and, if they join the program schools, discuss their potential and professional weaknesses. The managers request the elaboration of an Individual Plan of Perfection and Formation (PIAF) Aiming at professional development. The PEI schools organize weekly training sessions and are focused on the needs of professionals and students, promoting reflection on the practices developed in the school.